2020
DOI: 10.1007/s12325-020-01293-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety and Efficacy of Sitagliptin for Type 2 Diabetes Mellitus in Japan: Results of a Multicentre, Open-Label, Observational Post-Marketing Surveillance Study

Abstract: Introduction: A post-marketing surveillance (PMS) study was conducted to confirm the longterm risk-benefit profile of sitagliptin administered to Japanese patients with type 2 diabetes mellitus (T2DM) under real-world conditions. Methods: This prospective, multicentre, openlabel PMS collected data from 3326 patients receiving sitagliptin according to the approved indication during the case registration period (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In terms of effectiveness, the current study confirmed the glucose‐lowering effects of linagliptin use in Korean patients with T2D in a real‐world setting. The mean changes in HbA1c were similar to the results of the Japanese PMS studies, 9,10 a pooled analysis of data from Asian patients, 16 and PMS studies of other DPP‐4 inhibitors 13–15 . Our subgroup analysis also revealed that blood glucose levels were effectively reduced in all linagliptin‐treated patients categorized by various clinical factors.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In terms of effectiveness, the current study confirmed the glucose‐lowering effects of linagliptin use in Korean patients with T2D in a real‐world setting. The mean changes in HbA1c were similar to the results of the Japanese PMS studies, 9,10 a pooled analysis of data from Asian patients, 16 and PMS studies of other DPP‐4 inhibitors 13–15 . Our subgroup analysis also revealed that blood glucose levels were effectively reduced in all linagliptin‐treated patients categorized by various clinical factors.…”
Section: Discussionsupporting
confidence: 81%
“…The mean changes in HbA1c were similar to the results of the Japanese PMS studies, 9,10 a pooled analysis of data from Asian patients, 16 and PMS studies of other DPP-4 inhibitors. [13][14][15] Our subgroup analysis also revealed that blood glucose levels were effectively reduced in all linagliptin-treated patients categorized by various clinical factors. However, the glucose-lowering effects were more pronounced in patients with a shorter duration of T2D, lower BMI values, higher baseline HbA1c, no history of diabetic complications, no history of dyslipidaemia, and in those not using sulphonylureas at all.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…For example, in an observational post-marketing surveillance study, long-term sitagliptin use was not associated with additional safety concerns in type 2 diabetic patients. 80 Even if there were to be an increase in the systemic exposure of sitagliptin by twofold, it would be unlikely to result in any clinically relevant adverse event. 2,28 Even higher doses such as 800 mg single dose and 600 mg multiple doses have been shown to be tolerated well.…”
Section: Surrogate Techniques For In Vivo Bioequivalence (Be) Testingmentioning
confidence: 99%